Femoral rotation in total knee arthroplasty: a comparison of patient individualized jigs with gap balancing in relation to anatomic landmarks - Fitz, Wolfgang; Jäger, Sebastian; Rieger, Johannes Sebastian; Seebach, Elisabeth; Bitsch, Rudi G. (Knee surgery, sports traumatology, arthroscopy, 2017)
Purpose The purpose of our study was to compare the accuracy of the rotational position of the femoral component in total knee arthroplasty aligned with patient individualized jigs (PSJ) to a gap balancing technique (GBT).MethodsA consecutive series of 21 osteoarthritic patients were treated with 22 cruciate-retaining total knee prostheses. During surgery, the rotation of the femoral component pinholes was recorded for all knees using PSJ and GBT and transferred to computer tomograms (CT). The rotational differences between PSJ and GBT relative to the transepicondylar axis were analysed.ResultsThe medium rotation of the femoral component pinholes was 1.3° ± 5.1° (min = −6.3°; max = 14.4°) for PSJ and 0.1 ± 1.4° (min = −1.6°; max = 3.4°) for GBT. Outliers of more than 3° were found more frequently with PSJ in 12 cases but only in one for GBT.ConclusionBased on our study, we would not recommend relying intra-operatively solely on the CT-based PSJ without the option to adjust or control femoral rotation.Level of evidenceII.